The return of the king : being the third part of The lord of the rings - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (Lord of the rings, 2003)
As the Shadow of Mordor grows, the companions find their way through danger and mystery as they defeat the Dark Lord and celebrate Aragorn's ascent to become King of the West. 'Includes appendices containing genealogical and historical information that form the background of the story.